The Use Of Powerpoint Media On Interest In Learning PKN In Class IV SDN Batubantar - Laila Hayati (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2023)
This research aims to investigate the effect of media Power point use on the interests and outcomes of Civics in grade IV SDN Batubantar. This type of research is a qualitative descriptive study conducted at SDN Batubantar. The subjects of this study were teachers and fourth grade students. As for the object of this research is interest and learning outcomes through the use of power point media. Data collection techniques are used in the implementation of this research with interview techniques, observation and documentation. Checking the validity of the data is done by using triangulation techniques, namely by checking the information from interviews with documentation and observation. The results showed that it was significantly proven that learning using power point the media could have a positive effect on students' interest and learning outcomes in Civics lessons at SDN Batubantar. Therefore, it is recommended for classroom teachers to increase the use of media, one of which is power point media in Civics learning and other learning in order to increase student interest and learning outcomes.